2000
DOI: 10.1111/j.1095-9270.2000.tb01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of a wreck in the Red River, Choctaw County, Oklahoma, USA

Abstract: This paper reports the initial recording of an early riverboat wreck located in the Red River between Oklahoma and Texas. The wreck is probably the Caddo lost in 1842. The visible wreckage is described and the history of the Caddo is discussed. This is the earliest western rivers steamboat investigated by archaeologists to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The wreck's existence was brought to the attention of the Oklahoma Historical Society (OHS) in 1999. The name and date of the wreck were at first unknown, but its single-engine-with-flywheels configuration-a feature still evident despite the removal of much of the machinery-suggested a pre-1840 vessel, making it the earliest western river steamer yet examined by archaeologists (Lees and Arnold, 2000;Kane, 2004: 118-9). Besides its regional and national historical significance, the wreck also promised to yield insights into steamboat design and construction, and into the technology of early steam propulsion.…”
Section: The Steamboat Heroinementioning
confidence: 99%
“…The wreck's existence was brought to the attention of the Oklahoma Historical Society (OHS) in 1999. The name and date of the wreck were at first unknown, but its single-engine-with-flywheels configuration-a feature still evident despite the removal of much of the machinery-suggested a pre-1840 vessel, making it the earliest western river steamer yet examined by archaeologists (Lees and Arnold, 2000;Kane, 2004: 118-9). Besides its regional and national historical significance, the wreck also promised to yield insights into steamboat design and construction, and into the technology of early steam propulsion.…”
Section: The Steamboat Heroinementioning
confidence: 99%
“…A 15.24 m, (50 ft) portion of the vessel's stern was exposed above the river‐bottom sands, but the overall length of the hull could not be determined since the forward end was still buried. Machinery elements on the wreck, including the portside paddle wheel, the port and starboard main shafts, and a pair of centre‐mounted flywheels, indicated that the vessel was a western river‐type steamboat that likely dated to the late 1830s or early 1840s (Lees and Arnold, ). The site was designated ‘34Ch280’ in the Oklahoma archaeological inventory.…”
Section: Surveys and Test Excavations 1999–2002mentioning
confidence: 99%
“…A preliminary report on an unidentified steamboat wreck in the Red River of Oklahoma, USA was published in IJNA 29.1 (Lees and Arnold, ). Extensive archaeological and historical research has since been conducted by the Oklahoma Historical Society (OHS), the Center for Maritime Archaeology and Conservation (CMAC) at Texas A&M University (TAMU), and the Institute of Nautical Archaeology (INA).…”
mentioning
confidence: 99%